2021
DOI: 10.1111/bcpt.13549
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acetylsalicylic acid and pentoxifylline in guinea pigs with non‐alcoholic steatohepatitis

Abstract: Therapeutic options are urgently needed for non‐alcoholic fatty liver disease (NAFLD), but development is time‐consuming and costly. In contrast, drug repurposing offers the advantages of re‐applying compounds that are already approved, thereby reducing cost. Acetylsalicylic acid (ASA) and pentoxifylline (PTX) have shown promise for treatment of NAFLD, but have not yet been tested in combination. Guinea pigs were fed a high‐fat diet for 16 weeks and then continued on the diet while being treated with ASA, PTX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…In contrast to these findings, we have not previously been able to measure insulin resistance in the guinea pig model for NAFLD/NASH [ 28 , 40 ]. However, the control diet in the study of Podell and coworkers had a lower energy content (10.5 MJ/kg) compared to the LF-HSt (12.6 MJ/kg, Table S1 ) diet used as a control diet for this and previous studies in our group [ 26 , 28 , 29 , 30 , 40 , 51 ]. Considering the lower energy content as well as the higher amount of refined sugar in the high fat diet, the current study explored if insulin resistance could be induced by HFCS supplements in the drinking water while ensuring comparison to a low-calorie low-starch control group (LF-LSt, 11.2 MJ/kg).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast to these findings, we have not previously been able to measure insulin resistance in the guinea pig model for NAFLD/NASH [ 28 , 40 ]. However, the control diet in the study of Podell and coworkers had a lower energy content (10.5 MJ/kg) compared to the LF-HSt (12.6 MJ/kg, Table S1 ) diet used as a control diet for this and previous studies in our group [ 26 , 28 , 29 , 30 , 40 , 51 ]. Considering the lower energy content as well as the higher amount of refined sugar in the high fat diet, the current study explored if insulin resistance could be induced by HFCS supplements in the drinking water while ensuring comparison to a low-calorie low-starch control group (LF-LSt, 11.2 MJ/kg).…”
Section: Discussionmentioning
confidence: 83%
“…Consequently, the starch content of control diets applied in preclinical modeling might induce a metabolic state with little relevance to a healthy human control and—unintentionally—reduce the value of comparisons. For the guinea pig NAFLD/NASH model, a low-fat high-starch (LF-HSt) diet promotes a healthy liver phenotype, however guinea pigs do not display differences in weight or glucose tolerance compared to a HFD [ 26 , 27 , 28 , 29 , 30 ]. To investigate putative differences in a more metabolically relevant control group, a diet low in fat and starch was included (LF-LSt).…”
Section: Introductionmentioning
confidence: 99%
“…Liver sections for histology were fixed in 10% formalin and paraffin embedded prior to slicing in 2–4 µm thick sections and staining with hematoxylin and eosin (H&E) or picrosirius red (PSR) with Weigert’s hematoxylin solution. All histopathological scorings were performed in a randomized and blinded manner, as previously described for the guinea pig model and according to Kleiner et al [ 33 , 35 , 39 , 40 ]. The reliability of scoring was assessed by Cohen’s Kappa index [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it could be stated that the downregulation of ER stress and related protein expression by PTX can be attributed to its anti-inflammatory effect. However, in a Guinea pig-fed HFD-induced NAFLD model, pentoxifylline treatment for 8 weeks did not reduce steatosis, inflammation, and fibrosis (Ipsen et al, [ 81 ]. Surprisingly, PTX treatment (100 mg/kg) for 4 days/week for three weeks was shown to exacerbate fatty liver in obese and diabetic ob/ob mice by increasing intestinal glucose absorption and activating hepatic lipogenesis and it was suggested that PTX could aggravate fatty liver in patients with preexisting hyperglycemia (Massart et al, [ 82 ]).…”
Section: Antioxidants In Experimentally Induced Nafldmentioning
confidence: 99%